'Specimens of Bark Cloth, 1769': the travels of textiles collected on Cook's first voyage. (19th June 2018) - Thomas, Nicholas
Abstract: The voyages of Captain James Cook (1728–1779) inaugurated, among manifold historical processes, an encounter of textile traditions. Pacific Islanders were keenly interested in European fabrics; Europeans were fascinated by Oceanic textiles such as beaten bark cloth, which was extensively collected from Cook's first voyage onwards. Among manifestations of European interest, bark cloth sample books such as those produced as multiples by Alexander Shaw in 1787 have been a focus of research and curatorial activity in recent years. This essay considers a recently-identified book of specimens which pre-dates Shaw's by some fifteen years. It exemplifies a brief but seemingly intense European interest in Polynesian bark cloth, embracing the fabrics' technical, material, aesthetic, social and ritual aspects.